Hölderlin, Heidegger e a dimensão evocativa da palavra - Assis, Leandro Santos (Revista Eletrônica Estudos Hegelianos, 2021)
This article deals with some of Martin Heidegger's interpretations of Friedrich Hölderlin's poetry. After the turning of his thought (Kehre), the philosopher stopped to interpret certain original thinkers, such as Heraclitus and Parmenides, and some poets, such as Friedrich Hölderlin, Rainer Maria Rilke, Georg Trakl and Stefan Georg. This study seeks to examine Hölderlin's appropriation, notably regarding the square problem (Geviert), as well as the very instance of language as the man's home, which enabled Heidegger to make a qualitative leap in his analyzes. In this way, it is intended to elucidate decisive elements of the examination that very delineated the displacement of Heidegger's philosophy from existential analytics, above all, to the problem of language, namely: the appropriation of Hölderlin, not just any poet, but, the “poet of poets”.